Characterization of the molecular changes associated with the overexpression of a novel epithelial cadherin splice variant mRNA in a breast cancer model using proteomics and bioinformatics approaches: identification of changes in cell metabolism and an in - Rosso, Marina (2019)
Breast cancer (BC) is the most common female cancer and the leading cause of cancer death in women worldwide. Alterations in epithelial cadherin (E-cadherin) expression and functions are associated to BC, but the underlying molecular mechanisms have not been fully elucidated. We have previously reported a novel human E-cadherin splice variant (E-cadherin variant) mRNA. Stable transfectants in MCF-7 human BC cells (MCF7Ecadvar) depicted fibroblast-like cell morphology, E-cadherin wild-type downregulation, and other molecular changes characteristic of the epithelial-to-mesenchymal transition process, reduced cell-cell adhesion, and increased cell migration and invasion. In this study, a two-dimensional differential gel electrophoresis (2D-DIGE) combined with mass spectrometry (MS) protein identification and bioinformatics analyses were done to characterize biological processes and canonical pathways affected by E-cadherin variant expression.